Survey Perangkat Lunak Untuk Manajemen Big Data Menggunakan Metode SLR (Systematic Literature Review) - Muhammad Andryan Wahyu Saputra; Hamim Tohari; U'un Setiawati (Faktor Exacta, 2022)
Big data technology is a whole technology that can handle processing related to data analysis to explore the potential in it. Some uses of big data are based on the largest sources of data traffic, such as social media, financial transactions, public data, sensor data, and enterprise data. In the research conducted there is a problem, namely how to determine and find out the best software to manage big data. The following problems can be solved by conducting a software comparison survey to find out the best software that can be used and is suitable for big data management problems. The software survey research for big data management uses secondary data from national and international journals that have been published on Scopus, Semantic Scholar, and Google Scholar in the period 2017-2021 as data reference. The software survey in this study used the Systematic Literature Review (SLR) method. The results of research using SLR software state that the software that can be used to determine big data management is 7 software, Apache Hadoop software is software that is often used to perform big data analysis because Apache Hadoop software can have many features and managed to obtain the minimum results to maximize the results of the analysis so that this is different from the application of other software and also the application of software.